Legal Development for Electronic Evidence in Civil Litigation: Challenges and Future Expectations - Kusuma Daniel Kusnadi; Sidi Ahyar Wiraguna (LPPM Institut Pendidikan Nusantara Global, 2025)
The acceleration of digitalization in Indonesia’s judicial system has transformed civil procedural law evidence mechanisms to increasingly rely on electronic evidence. This study aims to analyze the legal construction and challenges of admitting electronic evidence in civil procedural law. Using a normative juridical approach, the study reviews regulations, jurisprudence, and legal doctrines related to electronic evidence. The population includes legislation and court decisions from 2020–2025, with purposive sampling of five selected cases. Data were analyzed through systematic normative interpretation. Findings indicate conditional recognition of electronic evidence, inconsistent jurisprudence, and a lack of adequate digital forensic technical guidelines. The burden of proof and role of IT experts remain unclear in practice. The study concludes that regulatory and technical guidelines need improvement to strengthen the principle of free proof and procedural justice in the digital era. Adoption of a digital chain of custody and verified electronic signatures is highly recommended.